Optimized Golgi-Cox Staining Validated in the Hippocampus of Spared Nerve Injury Mouse Model - Zhang, Jia-wei; Tabassum, Sidra; Jiang, Jin-xiang; Long, Cheng (Frontiers in Neuroanatomy, 2020)
Golgi-Cox staining has been used extensively in neuroscience. Despite its unique ability to identify neuronal interconnections and neural processes, its lack of consistency and time-consuming nature reduces its appeal to researchers. Here, using a spared nerve injury (SNI) mouse model and control mice, we present a modified Golgi-Cox staining protocol that can stain mouse hippocampal neurons within 8 days. In this improved procedure, the mouse brain was fixed with 4% paraformaldehyde and then stored in a modified Golgi-Cox solution at 37 ± 2°C. The impregnation period was reduced from 5–14 days to 36–48 h. Brain slices prepared in this way could be preserved long-term at –80°C for up to 8 weeks. In addition to minimizing frequently encountered problems and reducing the time required to conduct the method, our modified protocol maintained, and even improved, the quality of traditional Golgi-Cox staining as applied to hippocampal neuronal morphology in SNI mice.